2014
DOI: 10.1007/s00232-014-9757-6
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel Modulates the Delayed Rectifier Potassium Current (I K) and ATP-Sensitive Potassium Current (I KATP) in Human Breast Cancer Cells

Abstract: Ion channel expression and activity may be affected during tumor development and cancer growth. Activation of potassium (K(+)) channels in human breast cancer cells is reported to be involved in cell cycle progression. In this study, we investigated the effects of docetaxel on the delayed rectifier potassium current (I K) and the ATP-sensitive potassium current (I KATP) in two human breast cancer cell lines, MCF-7 and MDA-MB-435S, using the whole-cell patch-clamp technique. Our results show that docetaxel inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The three drugs mentioned above were reported to work by blocking the progression of the cell cycle, which ultimately led to the death of the cancer cells [ 51 , 52 ]. Paclitaxel and docetaxel might affect the proliferation of BRCA cells by modulating potassium currents, and TME could induce docetaxel resistance [ 42 , 53 , 54 ]. We concluded that KCNK1 could affect the cell cycle via potassium channels, thereby increasing drug sensitivity of BC patients to docetaxel, paclitaxel, and vincristine.…”
Section: Discussionmentioning
confidence: 99%
“…The three drugs mentioned above were reported to work by blocking the progression of the cell cycle, which ultimately led to the death of the cancer cells [ 51 , 52 ]. Paclitaxel and docetaxel might affect the proliferation of BRCA cells by modulating potassium currents, and TME could induce docetaxel resistance [ 42 , 53 , 54 ]. We concluded that KCNK1 could affect the cell cycle via potassium channels, thereby increasing drug sensitivity of BC patients to docetaxel, paclitaxel, and vincristine.…”
Section: Discussionmentioning
confidence: 99%
“…The mobility and potential difference between drug‐sensitive and drug‐resistant K562 cells demonstrated that acquired resistance to different drugs resulted in changes in electrophoretic mobility and zeta potential. This difference would imply possible distinguishable electrical properties between cell types . Even though there is not any statistically significant change in electrophoretic mobility between drug‐sensitive and drug‐resistant K562 cell lines (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…5), and paclitaxel can activate the voltage gated Ca 2þ channel CaV3.2 (6). Docetaxel was also found to modulate the activity of K þ channels known to regulate membrane potential and therefore Ca 2þ entry (7). Interestingly, the SK3 potassium channel has been found to be associated with oxaliplatin neurotoxicity (8), and we reported a pivotal role of this channel in the regulation of Ca 2þ homeostasis and Ca 2þ -activated proteases calpains (9,10).…”
Section: Introductionmentioning
confidence: 72%